2015
DOI: 10.1002/ppap.201400185
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thorns: Atmospheric Pressure Non‐Thermal Plasma Source for Dentistry Applications

Abstract: A novel atmospheric pressure, non-thermal plasma source -plasma thorns, can simultaneously generate plasma plumes toward multiple preset directions. This plasma source is proposed here for the sterilization of the inner surfaces of tubular structures. Compared with the highly directional plasma jets or jet arrays, the plasma thorns provides significantly higher antimicrobial efficacy in the radial directions. After treatment with plasma thorns of the root canal biofilm, a significant decrease in the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Further studies are necessary to elucidate if this feature can be advantageous for endodontic treatments. To increase the antimicrobial efficiency especially Plasma sources with an adapted geometry or the combination with mechanical treatment or a second cycle of plasma treatment should be investigated …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are necessary to elucidate if this feature can be advantageous for endodontic treatments. To increase the antimicrobial efficiency especially Plasma sources with an adapted geometry or the combination with mechanical treatment or a second cycle of plasma treatment should be investigated …”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of our laboratory, we showed that the adjunctive effect of atmospheric pressure plasma (APP) and disinfectant solutions surpasses the effect of the respective monotherapy . Furthermore, APP might penetrate into small cavities and kill bacteria . Although a limited effectiveness was evaluated using APP as a monotherapy, the combination of APP and disinfectant solutions may be a promising approach for root canal treatment …”
Section: Introductionmentioning
confidence: 99%
“…Plasma device sizes on the micrometer scale opens doors to many potential applications, such as the treatment of multiple internal cavities or complex hollow structures. This type of treatment can inhibit bacterial growth significantly in the root canal, resulting in maximum sterilization during dental treatments [ 61 ]. Odontophobia, i.e., dental fear, is the main reason behind children and some adults avoiding a visit to their dentist.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, plasma devices have been researched recently with promising results. A plasma-thorn device was fabricated and successfully used to inactivate B. aureus on Lactobacillus agar [ 61 ]. This in vitro result can be utilized for root canal treatment therapy.…”
Section: Plasma As a Novel Treatment Techniquementioning
confidence: 99%
“…A considerable number of works are devoted to this subject [1], because the application of microdischarge plasma is promising for the low-temperature treatment of materials. A number of devices have already been developed, which are intended for the treatment of oral cavity (e.g., dental bleaching [2], the improvement of the filling material density, mouth treatment [3][4][5], and others). There are also experimental data testifying to a possibility of successfully using plasma to treat living tissues in order to deactivate microorganisms [6], for sterilization [7], inactivation of cancer cells [8], to stop bleeding (for blood coagulation), to heal wounds, and so on.…”
Section: Introductionmentioning
confidence: 99%